Total knee Arthroplasty: risk factors for allogeneic blood transfusions in the South Asian population - Mufarrih, Syed Hamza (BMC Musculoskelet Disord, 2017)
BACKGROUND: Total knee arthroplasty (TKA) is the recommended treatment for end-stage knee osteoarthritis. Considering the various risks associated with intra and postoperative blood transfusions, better understanding is required with respect to the risk factors contributing to a greater possibility of blood transfusion during or after surgery. Although literature highlights several such factors, our study is among the first to identify these risk factors in the South Asian population which differs from other populations in several ways. METHODS: The study consists of a review of 658 patients undergoing TKA from 2005 to 2015. Data was obtained from patient medical records and was analysed using logistic regression analysis. The relationship between each predictor and the outcome variable was calculated as an Odds ratio (OR), the threshold of significance for which was p = 0.25 and p = 0.05 for univariate and multivariable analysis respectively. RESULTS: The mean age of the patient population was 63 years (78% female), 25% of whom received one or more blood transfusions. Multivariable analysis revealed 5 significant independent predictors for increased risk of blood transfusions including bilateral knee surgery (OR:5.51), preoperative anemia (OR:4.15), higher ASA (American Society of Anaesthesiologists) status (3–4) (OR:1.92), female sex (OR:3.44) and BMI (Body mass index) ≤30 (OR:1.79) while increasing co-morbidities and age (>60) were found to be insignificant. CONCLUSIONS: The factors identified for the South Asian population are largely similar to those for other populations. Identification of high risk patients will permit the application of an international multipronged approach which not only targets the modifiable risk factors but also the decision making process and blood management protocols in order to minimize the transfusion associated risks for a patient undergoing a TKA.